WOMEN’S RIGHTS AND MENSTRUAL LEAVE: THE INDIAN SCENARIO - Das, Juthika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Menstruation is a grossly neglected health issue in India. It is considered as a taboo, although menstruation is a natural biological process. Therefore, it is very difficult to openly discuss about menstruation in public places. As a result, majority of the women often go through the sufferings and pains of menstruation. Moreover, due to the attached stigma, it often becomes both health and psychological issue for girls and women primarily in developing countries. The question of menstrual hygiene management of adolescent girls in educational institutions, promotion of paid menstrual leave for working women etc. has often debated in different platforms. But, unlike countries like Japan, South Korea, Italy the legislative system of India is lagging behind in introducing the menstruation-friendly provisions and policies for women. This article is an attempt to address the issue of women’s right and menstrual leave in context of india.